Possible Associations between Bovine Growth Hormone Gene Polymorphism and Reproductive Traits - Maria Marina Unanian; Cristine Chaves Barreto; Célia Maria Torres Cordeiro; Alfredo Ribeiro Freitas; Luiz Antonio Josahkian (Brazilian Archives of Biology and Technology, 2002)
The polymorphism of the bovine growth hormone gene (bGH) was studied in 211 Nellore pure breed males for association with reproductive traits. Scrotal circumference and testosterone concentrations were collected monthly from 10 until 16 months of age. Additionally, testicular growth rates were calculated. DNA was amplified by PCR and digested using Msp I and Hae III restriction enzymes. Every polymorphism presented two alleles. The predominant alleles were D (0.85) and F (0.98), respectively, and genotype EE - bGH/Hae III was missing. Significant association (P<0.05) between bGH/Msp I polymorphism, scrotal circumference and testicular growth after puberty, as well as between bGH/Hae III and testosterone concentrations at puberty were detected. The results suggested that these association could be useful for selection, since bGH/Msp I and bGH/Hae III polymorphisms could be considered as markers for testicular development after puberty and onset of puberty, respectively. Em 211 machos da raça Nelore, PO, foi estudada a associação entre os polimorfismos do gene do hormônio de crescimento bovino (bGH) e características reprodutivas. Para o estudo foram realizadas medições mensais da circunferência escrotal e concentração de testosterona dos 10 aos 16 meses de idade e, ainda foi calculada a taxa de crescimento testicular. O DNA foi amplificado por PCR e digerido com as enzimas de restrição Msp I e Hae III. Cada um dos polimorfismos obtidos apresentou dois alelos. Os aleleo D (0,85) e F (0,98) predominaram na população estudada. Não foram encontrados animais portadores do genótipo EE do polimorfismo bGH/Hae III. Houve associação significativa (P<0,05) entre o polimorfismo bGH/Msp I, a circunferência escrotal e o crescimento testicular após a puberdade e, ainda, entre o polimorfismo do bGH/Hae III e a concentração da testosterona na puberdade. Os resultados sugerem que os polimorfismos bGH/Msp I e bGH/Hae III poderiam ser considerados marcadores do desenvolvimento testicular e o aparecimento da puberdade. Pela importância das observações, em função do reduzido tamanho da amostra, os estudos devem prosseguir.